Label-free detection of bladder cancer and kidney cancer plasma based on SERS and multivariate statistical algorithm - Bai, Xin; Lin, Juqiang; Wu, Xiang; Lin, Yamin; Zhao, Xin; Du, Weiwei; Gao, Jiamin; Hu, Zeqin; Xu, Qingjiang; Li, Tao; Yu, Yun (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2022)
Bladder cancer and kidney cancers are the two most common types of cancer in the urinary system. Here, a simple, accurate method of surface enhanced Raman spectroscopy (SERS) was proposed for label-free detection of bladder cancer and kidney cancer plasma. In addition, the SERS data was analyzed by combining three statistical algorithms of PCA-LDA, PLS-SVM and PLS-RF. The classification accuracy of the three diagnostic algorithms to classify the SERS spectra of bladder cancer and kidney cancer was 81.3%, 91.7%, and 98.4%, respectively. This exploratory work demonstrates that plasma SERS combined with PLS-SVM algorithm has superior performance in clinical screening of bladder cancer and kidney cancer. [Display omitted] •Label-free SERS method was employed to fast screening of bladder cancer and kidney cancer through peripheral plasma.•Three statistical algorithms: PCA-LDA, PLS-RF and PLS-SVM were used to for multi-classification analysis.•The advanced algorithm of PLS-SVM was achieved high accuracy for discriminate kidney cancer from bladder cancer. In this study, we mainly aimed to investigate the diagnostic potential of surface-enhanced Raman spectroscopy for bladder cancer and kidney cancer which are the most common cancers of the urinary system, and evaluate the classification ability of three statistical algorithms: principal component analysis-linear discriminate analysis (PCA-LDA), partial least square-random forest (PLS-RF), and partial least square-support vector machine (PLS-SVM). The plasma of 26 bladder cancer patients, 38 kidney cancer patients and 39 normal subjects was mixed with the same volume of silver nanoparticles, respectively, and then high-quality SERS signal was obtained. The SERS spectra in the range of 400–1800 cm−1 were compared and analyzed. There were some significant differences in SERS peak intensity, which may reflect the changes in the content of some biomacromolecules in the plasma of cancer patients. Based on the three algorithms of PCA-LDA, PLS-RF and PLS-SVM, the classification accuracy of SERS spectra of plasma from cancer patients and normal subjects was 98.1%, 100% and 100%, respectively. In addition, the classification accuracy of the three diagnostic algorithms to classify the SERS spectra of bladder cancer and kidney cancer was 81.3%, 91.7%, and 98.4%, respectively. This exploratory work demonstrates that SERS combined with PLS-SVM algorithm has superior performance for clinical screening of bladder cancer and kidney cancer through peripheral plasma.